Methemoglobinemia in Two Infants Brought to the Pediatric Emergency Department - Ayşegül Pala; Olena Erkun; Öner Özdemir; Zahir Şehmusoğlu (Southern Clinics of Istanbul Eurasia, 2021)
Methemoglobinemia is a complication that develops when ferrous hemoglobin is oxidized to a ferric state. It may be congenital due to structural hemoglobin defects or acquired through causes such as exposure to local anesthetic drugs or intake of toxins. Methemoglobinemia is characterized by cyanosis when the blood level exceeds 10%, and at higher levels it may cause tissue hypoxemia, coma, cardiovascular collapse, or even death. The primary mechanism used to reduce the methemoglobin level in the body is the nicotinamide adenine dinucleotide phosphate-cytochrome b5 reductase pathway. This case report is a presentation of the diagnosis and treatment of prilocaine-induced methemoglobinemia in 2 recently circumcised infants admitted to the pediatric emergency department.